An Overview of Epidemiology of COVID-19 in Macau S.A.R - Ieng, Sin Man; Cheong, Io Hong (Frontiers in Public Health, 2020)
The Greater Bay Area of southern China covers over 71millions population. The area is well connected with Hubei Province, the epicentre of COVID-19 outbreaks. Macau being one of the most densely populated city in the world, is very vulnerable to infectious diseases outbreaks. Since its sovereignty return to China 20 years ago, the city has experienced severe acute respiratory syndrome (SARS), Swine flu and COVID-19. At the time of writing, ten confirmed imported and local transmission cases were recorded. The government has taken series of measures to maintain 40 days free from new cases. In this article, we have described the ten confirmed cases and discussed the measures that the Macau Special Administrative Region (S.A.R.) government took in previous and current COVID-19 outbreaks.